2016
DOI: 10.4081/monaldi.2010.293
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Erythrocyte Superoxide Dismutase activity in patients suffering from asthma attacks

Abstract: Background. Oxidant-antioxidant imbalance may play an important role in the development and progression of bronchial asthma. However, the role of blood antioxidants especially in asthma exacerbation has not been fully discussed. Objective. This study examines a part of the intracellular antioxidant defense mechanism in asthmatic patients admitted to hospital due to severe exacerbation of their disease. Methods. Peripheral blood Erythrocyte Superoxide Dismutase (SOD) activity was measured in 38 patients (33 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…22 In addition, asthma attacks and oxidative stress may decrease peripheral blood erythrocyte superoxide dismutase activity and contribute to the consequence of cardiovascular diseases. 23,24 Our study showed a dose–response relationship between the number of asthma exacerbations and the development of PAD. This finding suggests that poor asthma control is the key factor associating with the PAD development.…”
Section: Discussionmentioning
confidence: 57%
“…22 In addition, asthma attacks and oxidative stress may decrease peripheral blood erythrocyte superoxide dismutase activity and contribute to the consequence of cardiovascular diseases. 23,24 Our study showed a dose–response relationship between the number of asthma exacerbations and the development of PAD. This finding suggests that poor asthma control is the key factor associating with the PAD development.…”
Section: Discussionmentioning
confidence: 57%
“…These interaction experiments did not stimulate cell death and release of cellular material as suggested by LDH measurements. The H 2 O 2 -poly(I:C) co-stimulation dose-dependently reduced gene and protein levels of SOD2 and partially SOD1, thus mimicking clinical findings of antioxidant deficiency at asthma exacerbation (40). This data supports the potential relevance of our in vitro model.…”
Section: Discussionmentioning
confidence: 76%
“…In this context, the study by Katsoulis and coauthors, included in this issue [11], showing decreased levels of erythrocyte SOD activity in patients suffering from an asthma attack and a significant correlation of erythrocyte SOD activity with functional parameters of patients at discharge, suggests a potential role for these measurements in monitoring the level of oxidative stress during asthma attacks and offers, as suggested by the authors, a potential approach for monitoring the health status and the pharmacological response of asthmatic patients.…”
Section: Oxidant-antioxidant Balance In Asthma and The Potential Of Amentioning
confidence: 86%